2021
DOI: 10.35608/ruraled.v41i3.1074
|View full text |Cite
|
Sign up to set email alerts
|

We Have Something to Say: Youth Participatory Action Research as a Promising Practice to Address Problems of Practice in Rural Schools

Abstract: The purpose of this article is to highlight a critical approach for practice, youth participatory action research, that can be used to invite rural youth to collaborate with school administrators, educators, and community leaders to identify and examine challenges, while building upon the strengths of a school and community to address challenges. Our youth participatory action research project was a collaboration between adult researchers and five students from a rural high school to examine and address postse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The project this group will create will try to respond to the problem they identified (see Table 4, Group F). Here, the use of YPAR allowed not only a clear identification of a problem, which could be identified using other data techniques, but also enabled young people to be involved in this identification and, from there, in action for change through the materialisation of their project (Cammarota & Fine, 2008; Means et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The project this group will create will try to respond to the problem they identified (see Table 4, Group F). Here, the use of YPAR allowed not only a clear identification of a problem, which could be identified using other data techniques, but also enabled young people to be involved in this identification and, from there, in action for change through the materialisation of their project (Cammarota & Fine, 2008; Means et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This allowed us to create space to focus on the central aim of this session, which was to identify aspects that they considered a priority for themselves and their contexts. This diagnosis allowed young people to explore their views of the surrounding community as experts and to respond to problems identified by designing projects for social change (Means et al, 2021). The following excerpts are an example of this: Mara: I can start; I wrote social isolation.…”
Section: Designing Projects For Their Communities: Ypar As a Tool To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In so doing, rural students with less college knowledge are directly exposed to post-secondary settings and provided access to information to help them make informed choices about their future, whether they opt for higher education, the military or immediate career immersion. Means et al (2021) demonstrated that rural SUCCs are an effective approach to address problems of practice in rural education by demonstrating the advantages of involving rural youth in participatory action research projects with school administrators, educators and community leaders to identify and examine district challenges. The researchers found that engaging rural youth in this capacity increased students' post-secondary education knowledge and their development as future rural leaders.…”
Section: School-university-community Collaborationsmentioning
confidence: 99%
“…Means et al (2021) demonstrated that rural SUCCs are an effective approach to address problems of practice in rural education by demonstrating the advantages of involving rural youth in participatory action research projects with school administrators, educators and community leaders to identify and examine district challenges. The researchers found that engaging rural youth in this capacity increased students’ post-secondary education knowledge and their development as future rural leaders.…”
Section: Capitalizing On Rural Cultural Wealthmentioning
confidence: 99%